Alchemy and a cup of tea : a cozy fantasy brewed with magic and romance - Thorne, Rebecca, 1991- (Thorne, Rebecca, 1991- Tomes and tea novel, 2025)
Bestselling author Rebecca Thorne brings the Tomes & Tea series to a delightful, cozy close for our beloved lesbian book- and tea- sellers. Reyna and Kianthe have no trouble commanding the Realm, running a bookshop, or rescuing baby dragons...but can they save their town from the swarming influx of...tourists?!? On the night of her kidnapping, all Reyna wanted was a relaxing cup of tea. She didn't expect to be dropped in a hidden prison cell, but what the hells. She's flexible. With appropriate fanfare, Kianthe "rescues" her wife...but Reyna's actually a terrible damsel in distress. Even worse, Reyna's cell was booby trapped with a mysterious alchemy circle. What does a radical alchemist want with the Arcandor's wife? And why did they think they could get away with this? While they investigate, another problem surfaces in their hometown. Word of New Leaf Tomes and Tea-and its celebrity owners-has finally spread. Tourists are everywhere, harassing the locals and ruining the charm of Tawney. As their friends struggle with the sudden influx, Kianthe and Reyna have to face a bigger conundrum than rogue alchemists: the fact that closing their bookshop might be the only way to save their town. Things can't just be simple, can they?